The Influence of Using Audio Visual Media on Listening Skills at Almuna Kindergarten - Santika, Cut; Fajrinur, Fajrinur; Zahra, Rita; Arviani, Venni (Riwayat: Educational Journal of History and Humanities, 2024)
This study aims to determine how much influence the development of children's skills through audio-visual media on early childhood in Almuna Kindergarten. This study uses the Classroom Action Research method. The collected data were analyzed qualitatively and quantitatively to identify the impact of the use of audio-visual media on the development of children's linguistic intelligence. The results of the study indicate that the use of audio-visual media has contributed to improving the intelligence of Skills in early childhood in Almuna Kindergarten, which shows that children's linguistic abilities have not been monitored. After the implementation of cycle I, the child's ability has reached 18.32%, it can be concluded that the child has developed but still needs improvement and further action. In cycle II there was an increase with an average value of 50.22%. This means that in cycle II the child's linguistic abilities have increased, so for perfection it is carried out in cycle III with that it is clear and developing very well with an average of 91.37%. And has met the previously determined criteria